Short selling and the development of anti-shorting laws in the UK - Mohamad, Azhar (Emerald, 2016)
The practice of short selling stocks can be traced back to the seventeenth century and has continued to thrive to this day. To short sell, one has to borrow the stock, sell it, and subsequently hope to buy it back at a lower price. Thus, the reason for shorting is to make a profit on the downfall when investors hold a bearish view on the stock. Too often, society associates shorting activity with market crashes and treats short sellers with hostility. This paper reviews the history of short selling and the development of anti-shorting laws, particularly with regard to the UK market. It also analyses the distinct literature on short selling. The paper argues that the development of anti-shorting laws shows that regulators are instituting a policy unfavourable to short sellers. The opposers of short selling may be seen as lacking ideas and having the tendency to ban anything they do not like. Short sellers, on the other hand, may be seen as the elite bodyguards of the financial market whose job it is to get rid of overvalued stocks, and ultimately keep the market safe and efficient. For this reason, short sellers deserve our praise and thanks, not our hatred and opprobrium.